House Season 6 Disc 5 - Laurie, Hugh, 1959-; Universal Studios Home Entertainment (Firm) (Universal City, CA : Universal Studios Home Entertainment, 2010)
House finds himself in an uncomfortable position: away from the examination room. As he works to regain his license and his life, his coworkers deal with the staff shakeups, moral dilemmas, and their own tricky relationships with House.
Knight fall -- Open and shut -- The choice -- Baggage -- Help me.
Title from container.
Release date: Aug. 31, 2010.
Bonus feature: Help me, episode commentary.
Hugh Laurie.
Rating: Not rated.
DVD ; anamorphic widescreen (1.78:1) ; Dolby digital 5.1 surround; region 1.
Keywords: Physician and patient -- United States -- Drama; Personality and occupation -- United States -- Drama; Hospitals -- Medical staff -- United States -- Drama; Hospital patients -- United States -- Drama; United States; Drama; Fiction television programs; Medical television programs; Video recordings for the hearing impaired; Television programs